Aplikasi Pembelajaran Mobile Berbasis Android sebagai Media Pendukung Pembelajaran Bola Voli: Studi Pengembangan Model 4D - Rizal Ardiansyah; Arie Rakhman (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to develop an Android-based learning application to support volleyball courses in higher education using the 4D development model consisting of define, design, develop, and disseminate stages. The research employed a Research and Development (R&D) approach involving 64 students from a Physical Education program. Research instruments included expert validation sheets for content and media, student feasibility questionnaires, and learning outcome tests in the form of pretests and posttests. The results of expert validation indicated that the application was highly feasible, achieving an average score of 89% in both material and media aspects. Student usability testing showed a feasibility level of 86%, indicating that the application was practical and user-friendly. Learning effectiveness analysis revealed a significant improvement in student achievement, with the average pretest score increasing from 54.53 to 83.34 in the posttest. The paired sample t-test produced a significance value of 0.000 (<0.05), confirming the effectiveness of the application in enhancing learning outcomes. Therefore, the developed Android-based learning application is appropriate and effective as a supplementary medium for volleyball instruction in higher education.